Three Amino‐functionalized Alkaline Earth Metal‐Organic Frameworks as Catalysts for Knoevenagel Condensation. Issue 37 (1st October 2020) - Song, Xiuduo; He, Yanzhen; Cai, Zhe; Li, Xiaoyun; Sun, Yanmin; Liu, Hongguang; Lu, Yanfei; Hou, Jie; Han, Enshan
Abstract: Three amino‐functionalized alkaline earth Metal‐Organic Frameworks (MOFs), including Mg‐ABDC [Mg(ABDC)(DMF)], Ca‐ABDC [Ca(ABDC)(DMF)] and Sr‐ABDC [Sr(ABDC)(DMF)]( ABDC=2‐aminobenzene‐1, 4‐dicarboxylate anion), were synthesized under solvothermal conditions. The incorporation of alkaline earth metals and N‐containing ligands is an effective way to increase the basicity of MOFs. To explore catalytic activity of three alkaline earth MOFs, they were applied to catalyze the Knoevenagel condensation of benzaldehyde with ethyl cyanoacetate to produce ethyl (E)‐α‐cyanocinnamate. All three alkaline earth MOFs had high catalytic performance, among which Mg‐ABDC showed the best performance. The activity of catalyst was expressed by the conversion rate and selectivity. The conversation rate was up to 94.7 % and the selectivity was nearly 100 % by adding Mg‐ABDC. Mg‐ABDC was proved to be an efficient, stable and heterogeneous catalyst through hot filtration and recycling tests. Abstract : Three amino‐functionalized alkaline earth Metal‐Organic Frameworks, including Mg‐ABDC, Ca‐ABDC and Sr‐ABDC, were synthesized by the self‐assembly of BDC‐NH2 and nitrate salts of alkaline earth metal under solvothermal conditions. All three amino‐functionalized alkaline earth MOFs as catalysts were studied on Knoevenagel condensation of benzaldehyde with ethyl cyanoacetate to produce ethyl (E)‐α‐cyanocinnamate. A detailed study of affecting the yield of ethyl (E)‐α‐cyanocinnamate was performed by changing the reaction parameters.